HUBUNGAN ANTARA FASILITAS KERJA, BEBAN KERJA DAN ETOS KERJA TERHADAP PRODUKTIFITAS KERJA PADA DEPARTEMEN INK SUPPLY SYSTEM PT. EPSON BATAM - MUSTAQIM .; ANDI SYAHRIL; ANDI NURMAN AZWAR; AGUS SAPUTRA; SINTIA . (LP2MTBM MAKARIOZ, 2023)
This study aims to obtain information about the relationship between the independent variables, namely; work facilities (X1), workload (X2), and work ethic (X3) with the dependent variable, namely employee work productivity (Y) of INK Supply System Department of PT Epson Batam, either individually or jointly.The population of this study is all employees of INK Supply System Department of PT Epson Batam, totalling 32 people. In this study, there is no classification of employee differences based on type or class status, both types of employment have the same treatment. Samples were taken using simple random sampling technique. The results showed that there was a significant positive effect of work facilities (X1), workload (X2), and work ethic (X3) on employee work productivity (Y) as indicated by the Fcount value of 30.799. This value is much smaller than the Fcount value at the 0.05 alpha significance level which is 2.95, or F = 30.799 < F0.05 (3:28) = 2.95. Thus, it means that the better the work facilities where employees work, the higher the workload of employees, and the higher the work ethic among employees, the higher the work productivity of these employees. The relationship pattern of the four variables expressed by the multiple regression equation = -11.443 + 0.497X1 + 0.079X2 + 0.937X3. Previously, based on validity and reliability tests, all instruments met the validity and reliability requirements. If calculated per variable, the variable that has the most influence is the work ethic variable, which has a coefficient of determination of 64.2%. This means that work ethic is the factor that most influences employee work productivity.